The association of adverse life events and parental mental health with emotional and behavioral outcomes in young adults with autism spectrum disorder. Issue 8 (2nd June 2021) - Hollocks, Matthew J.; Meiser‐Stedman, Richard; Kent, Rachel; Lukito, Steve; Briskman, Jackie; Stringer, Dominic; Lord, Catherine; Pickles, Andrew; Baird, Gillian; Charman, Tony; Simonoff, Emily
Abstract: People with autism spectrum disorder (ASD) are at increased risk of developing co‐occurring mental health difficulties across the lifespan. Exposure to adverse life events and parental mental health difficulties are known risk factors for developing a range of mental health difficulties. This study investigates the association of adverse life events, parental stress and mental health with emotional and behavioral problems in young adults with ASD. One hundred and fifteen young adults with ASD derived from a population‐based longitudinal study were assessed at three time‐points (12‐, 16‐, and 23‐year) on questionnaire measures of emotional and behavioral problems. Parent‐reported exposure to adverse life events and parental stress/mental health were measured at age 23. We used structural equation modeling to investigate the stability of emotional and behavioral problems over time, and the association between adverse life events and parental stress and mental health and emotional and behavioral outcomes at 23‐year. Our results indicate that exposure to adverse life events was significantly associated with increased emotional and behavioral problems in young adults with ASD, while controlling for symptoms in childhood and adolescence. Higher reported parental stress and mental health difficulties were associated with a higher frequency of behavioral, but not emotional problems, and did not mediate the impact of adverse life events. These results suggest that child and adolescent emotional and behavioral problems, exposure to life events and parent stress and mental health are independently associated, to differing degrees, with emotional or behavioral outcomes in early adulthood. Lay Summary: People with autism experience high rates of mental health difficulties throughout childhood and into adult life. Adverse life events and parental stress and mental health may contribute to poor mental health in adulthood. We used data at three time points (12‐, 16‐, and 23‐year) to understand how these factors relate to symptoms at 23‐year. We found that emotional and behavioral problems in childhood, adverse life events and parent mental health were all associated with increased emotional and behavioral problems in adulthood.